Enhancing human resource development as a strategic imperative for halal certification in food MSMEs - Harahap, Ade Khadijatul Z; Ramadhan, Muhammad; Harahap, Isnaini (Universitas Negeri Surabaya, 2024)
This study examines the challenges, solutions, and strategies related to human resource (HR) development in food MSMEs to obtain halal certification, particularly in regions such as North Sumatra, Padangsidimpuan City, South Tapanuli Regency, and Mandailing Natal Regency, where the number of halal-certified MSMEs remains limited. Despite having a large Muslim population, MSMEs in these areas face difficulties in tapping into the halal industry. The study identifies three main issues: limited HR capacity, low-quality HR, and lack of experience. Using the Analytic Network Process (ANP) method, the findings reveal that HR development through training and education is the most effective solution, although the level of agreement among informants is moderate. Additionally, the study proposes key strategies to address these challenges, including improving technical skills and fostering attitudes, work ethics, and knowledge, with a high level of agreement on these priorities.